1993
DOI: 10.1210/jcem.76.6.8501148
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized trial of gonadotropin-releasing hormone agonist plus estrogen-progestin or progestin "add-back" regimens for women with leiomyomata uteri.

Abstract: Treatment of women with myomas with GnRH agonists (GnRH-a) for 3-6 months will result in profound hypoestrogenism, a significant but temporary reduction in uterine volume, and menstrual suppression. Long-term (i.e. > 6 months) treatment with a GnRH-a is not recommended because of accelerated bone resorption and the presence of hypoestrogenic symptoms. In this 2-yr study, women with myomas were treated with GnRH-a plus one of two steroid "add-back" regimens to minimize adverse sequelae of chronic hypoestrogenis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 17 publications
0
21
0
1
Order By: Relevance
“…Contrary to previous understanding that leiomyoma growth is mainly estrogen related, recent data from clinical and in vitro studies indicate that progesterone plays a pivotal role (6,7). Some clinical studies have shown that synthetic progestins reverse the effect of GnRH agonists on leiomyoma volume, which indirectly indicates the effects of GnRH agonists on leiomyomata may be due partly to cessation of progesterone secretion (8). Furthermore, a reduction in mean leiomyoma volume was demonstrated in small, uncontrolled, clinical studies with the progesterone receptor antagonist mifepristone (9).…”
mentioning
confidence: 79%
“…Contrary to previous understanding that leiomyoma growth is mainly estrogen related, recent data from clinical and in vitro studies indicate that progesterone plays a pivotal role (6,7). Some clinical studies have shown that synthetic progestins reverse the effect of GnRH agonists on leiomyoma volume, which indirectly indicates the effects of GnRH agonists on leiomyomata may be due partly to cessation of progesterone secretion (8). Furthermore, a reduction in mean leiomyoma volume was demonstrated in small, uncontrolled, clinical studies with the progesterone receptor antagonist mifepristone (9).…”
mentioning
confidence: 79%
“…[14][15][16] PR-A and PR-B contents are higher in leiomyomas than in the adjacent myometrium with a significant dominance of PR-A over PR-B. 15,16 Evidence from clinical studies suggests that synthetic progestins stimulate leiomyoma growth, [17][18][19] whereas progesterone receptor antagonist (defined here as a progesterone receptor modulator, or PRM), RU-486 (mifepristone), has opposite effects. [20][21][22] RU-486 is the first PRM that was shown to decrease leiomyoma volume in clinical trials.…”
mentioning
confidence: 99%
“…In a prospective randomized trial of Gn-RH agonist plus estrogen-progesterone or progestin add-back regimens for women with uterine myomas, Friedman, Daly, Juneau-Norcross, Rcin, and Gleason (1 993) concluded that Gn-RH agonists addback regimens provide a useful long-term treatment strategy in women with large, symptomatic uterine myomas. They found that the estrogen-progesterone addback regimen was superior or equal to the progestin add-back regimen in efficacy and safety parameters assessed (Friedman et al, 1993). The value and safety o f long-term Gn-RH agonists and add-back therapy require further study.…”
Section: Medicalmentioning
confidence: 99%